The principle of legality in the social and democratic state of law: procedural expiration in direct reparation actions derived from the internal armed conflict - Roncancio Bedoya, Andres Felipe; Restrepo Marulanda, Mariana (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The present article addresses a review of two fundamental concepts for understanding the dynamics of administrative law and constitutional law, in which it addresses the scope of the principle of legality and whether the latter is integrated into a constitutional state, which implies that it is considered a principle of constitutionality, In the face of this, it is analyzed if this applied to a review of the procedural expiration in the processes of direct reparation derived from the internal armed conflict, generates a conditioning that implies a process of constitutionalization, as a consequence of this, it is necessary to carry out a review and budget the consequences of what this generates for the legal order interpreted in the light of the constitution.